1998
DOI: 10.1063/1.368760
|View full text |Cite
|
Sign up to set email alerts
|

Relation of coercivity to net magnetization in ferrimagnetically ordered Co/Gd multilayers

Abstract: Magnetization reversal processes in ferrimagnetically ordered Co/Gd multilayers were studied by means of the magneto-optical Kerr effect. Temperature dependencies of coercive field of the multilayers have been determined in the wide temperature region 25<T<300 K. An increase of temperature can cause both an enhancement and diminution of coercivity in the Co/Gd multilayers examined. Different temperature behavior of coercivity is explained by taking into account the temperature variation of net ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11] In thin films, magnetic configurations such as in-plane domain walls ͑DWs͒ appear due to the exchange coupling between the Gd and the TMs at the multilayer interfaces. [1][2][3][4][5][6][7][8][9][10][11] In thin films, magnetic configurations such as in-plane domain walls ͑DWs͒ appear due to the exchange coupling between the Gd and the TMs at the multilayer interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In thin films, magnetic configurations such as in-plane domain walls ͑DWs͒ appear due to the exchange coupling between the Gd and the TMs at the multilayer interfaces. [1][2][3][4][5][6][7][8][9][10][11] In thin films, magnetic configurations such as in-plane domain walls ͑DWs͒ appear due to the exchange coupling between the Gd and the TMs at the multilayer interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Значения коэрцитивной силы изучаемых образцов с увеличением температуры от 100 до 300 K уменьшаются. Обнаруженное изменение H C при T > 100 K подобно наблюдаемым для Fe/Gd и Co/Gd образцов в работах [14] и [15], соответственно. Согласно существующим данным, опубликованным в работах [14,15], такая зависимость H C (T ) свидетельствует о ферримагнитном характере изучаемых трехслойных систем, обусловленном изменением суммарного магнитного момента при изменении температуры [15].…”
Section: результаты исследований и их обсуждениеunclassified
“…Deposition temperature effect on multilayer structure was observed. Magnetization reversal process was also studied in Co/Gd multilayers by means of the magneto-optical Kerr effect [4]. Temperature dependence of coercive field of the multilayers has been determined in the wide temperature region 25 K < T < 300 K. It was observed that an increase of the temperature caused either the enhancement or diminution of coercivity in the examined Co/Gd multilayers depending on bilayer thickness.…”
Section: Introductionmentioning
confidence: 99%